Coeffect of different core–shell particles and β nucleating agent on the mechanical and thermal properties of polypropylene random copolymer composites. (March 2016) - Li, Youchen; Lin, Fangqin; Cui, Xiaoqian; Guo, Weihong
The coeffect of β-nucleating agent (β-NA) and different core–shell particles (CSPs) on improving the mechanical properties and thermal stability of polypropylene random copolymer (PPR) composites were investigated. Different CSPs, that is, the regular POE/nano-calcium carbonate (CaCO3 ) and the novel PE/nano-CaCO3 CSP were prepared through melt blending. The transmission electron microscopic micrograph demonstrated that the core–shell structure was successfully prepared and the CSP dispersed homogeneously in the PPR matrix. β-NA was also introduced into the PPR matrix to control the crystalline structure. The results of differential scanning calorimetry, wide-angle x-ray diffraction, and polarization optical microscopy showed that the relative content of β-form crystal was greatly enhanced in the presence of β-NA. The results of the mechanical tests and thermal gravimetric analysis indicated that the comprehensive mechanical properties and thermal stability were all greatly improved, especially for the sample with the incorporation of both β-NA and PE/nano-CaCO3 CSP.